Role of the Multidrug Efflux System MexXY in the Emergence of Moderate Resistance to Aminoglycosides among Pseudomonas aeruginosa Isolates from Patients with Cystic Fibrosis - Vogne, Christelle (American Society for Microbiology, 2004)
This study investigates the role of active efflux system MexXY in the emergence of aminoglycoside (AG) resistance among cystic fibrosis (CF) isolates of Pseudomonas aeruginosa. Three genotypically related susceptible and resistant (S/R) bacterial pairs and three other AG-resistant CF strains were compared to four non-CF strains moderately resistant to AGs. As demonstrated by immunoblot experiments, pump MexY was strongly overproduced in all of the resistant bacteria. This MexXY upregulation was associated with a 2- to 16-fold increase in the MICs of AGs in the S/R pairs and lower intracellular accumulation of dihydrostreptomycin. Alterations in mexZ, the repressor gene of operon mexXY, were found in all of the AG-resistant CF isolates and in one non-CF strain. Complementation of these bacteria with a plasmid-borne mexZ gene dramatically reduced the MICs of AGs, thus highlighting the role played by MexXY in the development of moderate resistance in CF patients. In contrast, complementation of the three non-CF strains showing wild-type mexZ genes left residual levels of resistance to AGs. These data indicate that a locus different from mexZ may be involved in overproduction of MexXY and that other nonenzymatic mechanisms contribute to AG resistance in P. aeruginosa.